"Like a nurse but not a nurse": Clinical Research Practitioners and the evolution of the clinical research delivery workforce in the NHS - Rachel Faulkner-Gurstein; Helen C. Jones; Christopher McKevitt (BMC, 2019)
Abstract Background Clinical research is increasing across the United Kingdom. Within the context of a shortage of nurses, trusts have struggled to maintain research capacity. In order to meet staffing demands, trusts have increasingly turned to Clinical Research Practitioners (CRPs) to assist in the delivery of clinical research. Initially an ad hoc workforce, the CRP role is being formalised and professionalised. This study is a close examination of the clinical research delivery workforce at one research-intensive acute trust in the United Kingdom, with a focus on the emerging CRP staff group. Methods The study was conducted in a large inner-city teaching hospital (acute trust) in London, United Kingdom. Data were collected between September and December 2017. Twenty-five staff were interviewed across 11 different directorates. Interviews were semi-structured with an overall focus on research staff backgrounds and roles, as well as their perceptions and experiences of careers in research. The data were managed using NVivo 11 software and analysed thematically. Results CRPs are drawn from a wider pool of educational and employment backgrounds than their nurse colleagues, and actively seek out work in health research. CRPs receive on-the-job training to acquire the competencies that are necessary for them to carry out their work. The CRP role, which began in an ad hoc manner, has become regularised, yet remains to be well defined, which can be a source of frustration for CRPs and those who work with them. Conclusions The professionalisation of the CRP workforce represents an opportunity for the health research system to employ research workers who possess a range of in-demand skills and to shore up research capacity in the context of the shortage of nurses.